The Impact of Religiosity on the Malaysian Muslim Community’s Attitude Towards the Practice of Cupping - Hamza Abed Alkarim Hammad; Hasanah Abd Khafidz; Irwan Mohd Subri (Institut Agama Islam Negeri Batusangkar, 2024)
Vol. 22 No. 1